Salmonella enterica in South American sea lions (Otaria byronia) from the north coast of San Matías Gulf (Patagonia, Argentina) - Origlia, Javier Aníbal (2021)
There is little information about the diseases that can affect the Argentine populations of pinnipeds. Salmonellosis has been described in marine mammals of different regions of the world. The aim of this study was to detect the presence of Salmonella enterica in pinnipeds that inhabit the marine littoral zone of Río Negro province (Argentina) during the breeding season, the serovars circulation and the antimicrobial susceptibility.